Mesenteric Ischemia - Shannon Toohey (eScholarship Publishing, University of California, 2016)
Audience: This simulation session is appropriate for emergency medicine residents at any level or medical students. Introduction: Mesenteric ischemia is a rare, but serious cause of abdominal pain. Practitioners must recognize the diagnosis quickly. The clinical course rapidly advances from bowel ischemia to infarction, sepsis, and frequently death. Mesenteric ischemia accounts for approximately 1% of all ED cases of abdominal pain in the elderly, but the mortality is as high as 93%. Objectives: At the end of this simulation session, the learner will: 1) Recognize signs and symptoms of mesenteric ischemia; 2) order appropriately imaging and labs in the workup of an elderly patient with abdominal pain; 3) manage a patient with mesenteric ischemia, a rare, but serious cause of abdominal pain in the elderly; 4) discuss anchoring bias, specifically related to patients referred to the ED with an established diagnosis by outside specialists. Methods: This educational session is a high-fidelity simulation.